Del Río Hortega’s insights into oligodendrocytes: recent advances in subtype characterization and functional roles in axonal support and disease - López-Muguruza, Eneritz; Peiró-Moreno, Carla; Pérez-Cerdá, Fernando; Matute, Carlos; Ruiz, Asier (Frontiers in Neuroanatomy, 2025)
Pío Del Río Hortega (1882–1945) was a giant of modern neuroscience and perhaps the most impactful member of Cajal’s School. His contributions to clarifying the structure of the nervous system were key to understanding the brain beyond neurons. He uncovered microglia and oligodendrocytes, the latter until then named mesoglia. Most importantly, the characterization of oligodendroglia subtypes he made has stood the omics revolution that added molecular details relevant to comprehend their biological properties. Astounding as it may seem on today’s eyes, he postulated a century ago that oligodendrocytes provide trophic support to axons, an idea that is now beyond doubt and under scrutiny as dysfunction at the axon-myelin unit is key to neurodegeneration. Here, we revised recent key advancements in oligodendrocyte biology that shed light on Hortega’s ideas a century ago.